Intellectual Disability and Blended Phenotypes: Insights from a Centre in North India - Inusha Panigrahi; Sudha Rao; Shalu Verma Kumar; Divya Kumari; Parminder Kaur (Case Reports in Genetics)
Intellectual disability (ID) is seen in around 2.5% of global population and can vary from mild to severe and profound ID. There can be multiple affected family members if it is inherited, though many autosomal dominant ID cases would be due to de novo mutations are very less likely to recur in families. A confirmatory diagnosis is facilitated by genetic testing like chromosomal microarray and next generation sequencing. We describe here our cohort of 15 patients: children and adolescents with ID diagnosed by using sequencing technologies and parental segregation studies. Most of the variants identified were de novo variants and consistent with sporadic occurrence, and blended phenotypes were identified. Appropriate genetic counseling was performed and options for prenatal diagnosis were discussed. Thus, advanced sequencing technologies enable identification of likely causative de novo variants associated with intellectual disability and dysmorphism.